2021
DOI: 10.35940/ijitee.k9503.09101121
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Entity Resolution Approach for Big Data

Abstract: Entity Resolution (ER) is defined as the process 0f identifying records/ objects that correspond to real-world objects/ entities. To define a good ER approach, the schema of the data should be well-known. In addition, schema alignment of multiple datasets is not an easy task and may require either domain expert or ML algorithm to select which attributes to match. Schema agnostic meta-blocking tries to solve such a problem by considering each token as a blocking key regardless of the attributes it appears in. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Likewise, in [15], the authors have discussed big data's challenges to entity resolution and proposed a hybrid www.ijacsa.thesai.org similarity measurement approach based on traditional syntactic and word-embedding approaches. In [16], Abd El-Ghafar et al have suggested an entity resolution approach for big data based on hashing TF and Jaccard similarity. The approach was applied to seven scenarios where different Natural Language Processing (NLP) techniques were used to show the impact of these techniques on entity resolution.…”
Section: Related Workmentioning
confidence: 99%
“…Likewise, in [15], the authors have discussed big data's challenges to entity resolution and proposed a hybrid www.ijacsa.thesai.org similarity measurement approach based on traditional syntactic and word-embedding approaches. In [16], Abd El-Ghafar et al have suggested an entity resolution approach for big data based on hashing TF and Jaccard similarity. The approach was applied to seven scenarios where different Natural Language Processing (NLP) techniques were used to show the impact of these techniques on entity resolution.…”
Section: Related Workmentioning
confidence: 99%